Bridging Healthcare Disparities: Lessons from Volunteering in Guatemala - Banhart, Maggie E. (My University, 2024)
Global healthcare disparities are clear, particularly in under-developed countries like Guatemala, where access to basic medical services remains a significant challenge for many. My summer spent in Guatemala provided a unique opportunity to engage directly with these disparities, offering healthcare support to poverty-stricken rural communities, as well as volunteering at a special needs facility. Immersed in a culture vastly different from my own, I was confronted with the realities of living and working in a healthcare system with limited resources, contrasting firmly with the system I have known in the United States. This experience not only highlighted the significant gaps in healthcare access and quality between the two countries, but also emphasized the importance of understanding a culture to providing effective care. As I navigated the difficulty of cross-cultural communication and adjusted to the challenges of foreign healthcare conditions, I gained invaluable insights into the social factors of health and the toughness of communities facing adversity. This paper explores my journey through the lens of these experiences, analyzing the cultural and healthcare differences I encountered, and reflecting on the huge impact this immersion has had on my understanding of global health and my development as a future healthcare professional.